Thermal Performance Evaluation of Traditional Buildings Flat Roofs in a Hot and Arid Climate of Algeria - M'hamed Mahdad; Aghiles Hammas; Said Abboudi (Journal of Architectural and Engineering Research)
This investigation aims to apply the analytical method of admittance for determining the thermal performance of composite flat roofs in traditional houses located in the southern region of Algeria,  characterized by hot and arid climate conditions. The effect of adding insulation to the composition of flat roofs in traditional houses is studied by varying its, type, location and thickness. In this study, nine configurations of composite flat roof systems were manufactured using multiple layers with five types of insulations. Moreover, different dynamical thermal parameters are analyzed in this study, namely time lag (TL), decrement factor (DF), admittance (Y), transmittance (U), and surface factor (SF). The main results revealed that the roof configuration of R8 with insulation based on formaldehyde board presents a high value of TL (9.94 hours) and the lowest value of DF (0.1). In contrast, the configurations without insulation addition (R1, R2, and R3) display the lowest values of TL (4.91, 4.74, and 4.81, respectively) and the highest values of DF (0.59, 063, and 0.62, respectively). This research is useful for clearly understanding the thermal performance of composite flat roofs for the improvement of the energetic efficiency of traditional buildings.